Paired neurophysiological and clinical study of the brainstem at different stages of Parkinson's Disease. Issue 10 (October 2015) - de Natale, E.R.; Ginatempo, F.; Paulus, K.S.; Manca, A.; Mercante, B.; Pes, G.M.; Agnetti, V.; Tolu, E.; Deriu, F.
Highlights In comparison with matched controls, VEMPs were consistently altered in patients with Parkinson's Disease (PD) and severity of abnormalities progressively increased with stage of disease. In PD significant correlation was found between VEMP alterations and both postural instability and REM sleep behavior disorder. Combined use of VEMPs may provide insights into pathophysiological dynamics of brainstem involvement at the earliest phases of PD.